Investigation of the viscosity and density of heavy oil/water blends at elevated temperatures and pressure; Part 1: Oil-only sample (absence of water). (1st September 2018) - Modaresghazani, J.; Moore, R.G.; Mehta, S.A.; Van Fraassen, K.C.; Ursenbach, M.G.; Van Dorp, Johan; Laureshen, Catherine J.
Abstract: A proprietary cell was designed and fabricated to investigate the density and viscosity of fluid at high pressure and elevated temperatures. In the first part of this study the results of density and viscosity measurement of a heavy oil sample in the absence of water are presented and the results for water/oil blends will be reported in the second part. A heavy oil from a reservoir in Western Alberta was used and its density and viscosity were measured using a special blind cell and a custom made inline viscometer respectively at pressure of 13.76 MPa (2000 psig) and elevated temperatures of up to 300 °C. Hysteresis was observed on density and viscosity of the heavy oil when it was cooled down after being exposed to elevated temperatures.